Geografías urbanas, arte y memorias colectivas: el Centenario chileno y la definición de lugar - Cortés Aliaga, Gloria; Herrera Muñoz, Francisco (El Colegio de México, A.C., 2010)
The identification metaphors during the celebration of the independence centenary in Chile were defined by partisan discourses, access to modernity, and opposition to the political, cultural, and social system originated during the nineteenth century. On the one hand, this territorial definition gave place to a rhetoric of landscape according to a social critique containing the paradigms of time and space. On the other hand, it fostered the definition of spaces of power, where festivities, popular activities, and the erection  of monuments delimit territorial politics and the symbolic construction of Chilean oligarchy. Reading these expressions would explain the position occupied by social subjects and their territorial affirmation after 1910.